The design of speaking materials for hospitality students of Trans Ocean Floating Hotel program based on competency based language teaching approach - Desi Ratnasari; Arbain Arbain (Journal of English Language and Pedagogy, 2019)
The objectives of this study are to (1) describe the designing of speaking materials for hospitality students in Trans Ocean Floating Hotel Program based on Competency-Based Language Teaching. (2) Reveal the efficacy of the speaking teaching materials in improving students communication skills. This research belongs to Educational Research and Development (R&D) using a simplified six steps of Borg and Gall’s model (1983). The six steps are as follows. (1) Research and information collecting was conducted by performing document analysis, class observation, interview, product testing, as well as experts’ judgments, (2) Planning and drafting, (3) Draft revision by experts, (4) Field testing which was conducted in basic class of the Trans Ocean Floating Hotel Program, (5) Revision, and (6) Final product. The technique of collecting data used in this research consists of (1) document analysis, (2) classroom observation and (3) interview. It was made for obtaining the data for the target situation analysis and appropriateness of the design speaking materials for hospitality students. The findings show that (1) learning materials that were designed in this research fulfilled the criteria of the R&D model, which is based on the students’ need lack and want. The purpose of the learning is preparing the students in their future job field as hotel staff and need to learn more about speaking because speaking skill is more useful for working as hotel staff. (2) The efficacy of the speaking materials is that it serves the explicit instruction and encourage the students in doing activities, especially speaking, besides, there are various activities in the textbook. This textbook is designed based on the Trans Ocean Floating Hotel student’s need, lack, and want. Furthermore, the speaking materials as the product of this study provide additional learning resources for students.